A MULTI CRITERIA APPROACH TO DESIGNING THE CELLULAR MANUFACTURING SYSTEM - Rika Ampuh Hadiguna (Institute of Research and Community Outreach - Petra Christian University, 2005)
Cellular manufacturing system design problems such as design framework, manufacturing cells layout and layout evaluation. The research objective is developing the framework to designing manufacturing cells with considering the organization and management aspects in shopfloor. In this research have compared the existing layout with proposed layout which applied the multi criteria approach. The proposed method is combining Analytical Hierarchy Process (AHP), Clustering and heuristic approach. The result has show that grouping with Single Linkage Clustering (SLC) to be selected as manufacturing cells. The comparison of clustering weight is 0,567, 0,245 and 0,188 for SLC, Complete Linkage Clustering (CLC) and Average Linkage Clustering (ALC), respectively. This result shows that generating layout by using grouping result from SLC. The evaluation result shows that types of manufacturing cells better than process layout which used the existing system.